2021
DOI: 10.1111/jcmm.16376
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of miR‐188‐5p alleviates hepatic fibrosis by significantly reducing the activation and proliferation of HSCs through PTEN/PI3K/AKT pathway

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 37 publications
(26 citation statements)
references
References 59 publications
0
22
0
Order By: Relevance
“…We found that PTEN was predicted to be the target of miR-616-3p and the direct binding relationship was confirmed by dual luciferase assays. PTEN is a tumor-suppressor gene with specific phosphatase activity and plays important roles in cell growth, proliferation, and migration via the PI3K-AKT pathway 30 , 31 . Studies have shown that PTEN expression was decreased both in endometriosis tissue and in primary cultured endometrial stomal cells, which contributed to cell proliferation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…We found that PTEN was predicted to be the target of miR-616-3p and the direct binding relationship was confirmed by dual luciferase assays. PTEN is a tumor-suppressor gene with specific phosphatase activity and plays important roles in cell growth, proliferation, and migration via the PI3K-AKT pathway 30 , 31 . Studies have shown that PTEN expression was decreased both in endometriosis tissue and in primary cultured endometrial stomal cells, which contributed to cell proliferation 32 .…”
Section: Discussionmentioning
confidence: 99%
“…We found PTEN was predicted to be the target of miR-616-3p and the direct binding relationship was con rmed by dual luciferase assay. PTEN is a tumor-suppressor gene with speci city phosphatase activity, and plays important roles in cell growth, proliferation and migration via PI3K-AKT pathway [25,26]. Studies showed PTEN expression was decreased in both endometriosis tissue and primary cultured endometrial stomal cells, which contributed to cell proliferation [27].…”
Section: Discussionmentioning
confidence: 99%
“…miR-129-5p negatively regulates HSC activation induced by paternally expressed gene 3 (PEG3) [ 100 ]. Inhibition of miR-188-5p alleviates liver fibrosis by suppressing HSC activation through the PTEN/PI3K/Akt pathway [ 101 ].…”
Section: Association Of the Causes Of Liver Cirrhosis And Mirnasmentioning
confidence: 99%